2019
DOI: 10.11114/afa.v5i2.4253
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Internally Generated Revenue on Budget Implementation in Ekiti State

Abstract: The study examined the effect of internally generated revenue on budget implementation in Ekiti State. Specifically the study analyzed trends of components of internally generated revenue in Ekiti state including taxes, fines & fees, licenses, earnings and sales, interest and dividend, evaluated the relative impact of internally generated revenue components on budget implementation, and also analyzed the causal relationship between internally generated revenue components and budget implementation in Ekiti stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…For instance, [13] studied the challenges to capital budget implementation in Nigeria using a descriptive survey of 200 respondents in 20 federal ministries, departments and agencies within two states in the South-south geopolitical zone and concluded that budget presentation by the presidency as well as delays in approval by the national assembly, leakages associated with corruption poor monitoring and evaluation of the budget were significant factors militating against effective capital budget implementation in Nigeria. [14] also studied the effect of internally generated revenue on budget implementation in Ekiti State and discovered that there is no causal relationship between components of internally generated revenue. The statutory allocation and budget implementation of the six states of Southwest Nigeria for a period of 10 years spanning from 2008 to 2017 was investigated by [15] and findings revealed that though impact of statutory allocation on actual expend-iture is positive, such impact is not significant in the context of southwest states, and that past period statutory allocation to southwest states does not significantly depict the level of budget implementation in the current period…”
Section: Overview Of Budgeting Challenges Globally and In Nigeriamentioning
confidence: 99%
“…For instance, [13] studied the challenges to capital budget implementation in Nigeria using a descriptive survey of 200 respondents in 20 federal ministries, departments and agencies within two states in the South-south geopolitical zone and concluded that budget presentation by the presidency as well as delays in approval by the national assembly, leakages associated with corruption poor monitoring and evaluation of the budget were significant factors militating against effective capital budget implementation in Nigeria. [14] also studied the effect of internally generated revenue on budget implementation in Ekiti State and discovered that there is no causal relationship between components of internally generated revenue. The statutory allocation and budget implementation of the six states of Southwest Nigeria for a period of 10 years spanning from 2008 to 2017 was investigated by [15] and findings revealed that though impact of statutory allocation on actual expend-iture is positive, such impact is not significant in the context of southwest states, and that past period statutory allocation to southwest states does not significantly depict the level of budget implementation in the current period…”
Section: Overview Of Budgeting Challenges Globally and In Nigeriamentioning
confidence: 99%